ODC1-associated astrocytic urea cycle dysregulation in age-related memory impairment - Mengna Wu; Shengyao Zhang; Xi Zhao; Bingyu Zhang; Guoran Wan; Jie Gui; Meng Zhang; Baoxue Yang; Dilong Chen; Guoli Li; Qiu Chen; Boyue Huang; et al. (Biogerontology, 2026)

PAN4, an AI-designed host-directed immunomodulatory peptide, promotes PGRP-SC1a-associated intestinal immune homeostasis in Drosophila melanogaster - Yanying Sun; Yanan Wei; Wenjie Jia; Xinyue Zhou; Ran Dong; Zekun Wu; Hongyu Miao; ZhenZhi Li; Zheng Chen; Chaoran Liu; Weijie Yuan; Ying Hu; et al. (Insect Biochemistry and Molecular Biology, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Radio frequency-enhanced remediation of PAHs-contaminated soils using peroxydisulfate: Performance and mechanistic insights - Wenhao Qi; Anxu Sheng; Dawei Lan; Zezhou Zhao; Yao Shi; Fengjiao Zhang; Jiang Lin; Ying Ran; Wei Lou; Jing Chen; Xiaohui Wu; Linling Wang (Journal of Environmental Management, 2026)

Asymmetric spectral modulation of bioinspired Janus metafabric toward environment-adaptive thermal and moisture management under extreme conditions - Yang Wu; Long Zhang; Hao-Ran Yang; Jiaqi Li; Yuzhen Hou; Chang-Shun Li; Bobo Shi; Meng Zhou; Wulin Shang; Weiqing Kong; Huan Xu; Gang Zhou; et al. (Chemical Engineering Journal, 2026)

Construction of bioaffinity antibacterial coatings via piezoelectric effect-enhanced alkaline microenvironment - Zhe Hao; Cong Wu; Ning Zhao; Ran Liu; Guolu Mu; Yufei Tang (Chemical Engineering Journal, 2026)

The Cangshan Mountain Precipitation Experiment (CAMPEX): Modulation of Precipitation by Typical Steep Mesoscale Terrain over Southwest China - Jian Li; Yin Zhao; Gaili Wang; Anlun Xu; Mengke Zhang; Tao Zhang; Baoju Dong; Guotao Zhang; Jian Huang; Yu Li; Cheng Yang; Bin Shu; et al. (Journal of Meteorological Research, 2026)

A simple method to estimate seismic subsidence in soft soil under amplitude non-stationary seismic action - Gan-Ling Xian; Jing-Yan Lan; Li-Chun Chen; Yong-Zhi Wang; Lei Wang; Zhao-Ran Wu (Engineering Geology, 2026)

Recent advances in ionotropic GABA receptor antagonists: A comprehensive review of design strategies and structure-activity relationships - Qi Zhang; Yifei Wu; Xiaojing Duan; Jinjin Tao; Ran Zhao; Jiaxi Guo; Jianyong Li (Pesticide Biochemistry and Physiology, 2026)

Photothermal-responsive Au nanorod-silica nanocomposite with on-demand curcumin release for sequential therapy of biofilm infections - Wenhui Jiang; Shunlan Luo; Kehan Du; Kai Yuan; Yuanhua Cong; Xiaoping Zeng; Dawei Wang; Hongyang Zhao; Huinan Suo; Liu Yang; Xiaowen Ou; Hao Jiang; et al. (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

A remote sensing framework unveiling the life-cycle dynamics and environmental drivers of Ulva prolifera green tides in the South Yellow Sea - Yijie Tang; Mengquan Wu; Jie Zhao; Shaopeng Luan; Pengsen Yang; Longxing Liu; Bowen Liu; Jinyi Lv; Gang Chen; Hongyu Kan; Yuying Ran; Huining Lai (Marine Environmental Research, 2026)

AnchorReF: A novel anchor-based visual re-localization framework aided by multi-sensor data fusion - Hao Wu; Yu Ran; Xiaoxiang Zhang; Xinying Luo; Li Wang; Teng Zhao; Yongcheng Song; Zhijun Zhang; Huisong Zhang; Jin Liu; Jian Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Impacts of Vegetation Restoration during Urbanization on Soil Organic Carbon Fractions: Dynamics and Stability - Fenai Lei; Hongkai Liao; Hongjie Chen; Kaixiang Zhan; Han Wu; Taishan Ran; Yuxin Zhao (Journal of Soil Science and Plant Nutrition, 2026)

Seismic data processing key technology for coalbed methane reservoir - Ming Zhang; Bao-yin Zhao; Zhi-fang Ran; Wen-wu Shi; Hao Li; Kai-long Wu; Gen-yang Tang (Applied Geophysics, 2026)

Metrnl in health and disease: tissue-specific actions and signaling networks - Ran Zhao; Yue Qi; Pan Li; Zhe Zhang; YiYang Chen; Xiaopeng Wu; Wei Wang; Xiaoqing Guo; Huadong Zhao; Yang Yang; Xiaowu Wang (Apoptosis, 2026)

Unveiling the molecular mechanisms of dihydromyricetin regulating the biosynthesis of three key secondary metabolites in Monascus purpureus HBSD08 through integrated transcriptomic and metabolomic analyses - Ran Fang; Yingying Wang; Jie Qiao; Di Wu; Qianyu Gao; Chunzheng Han; Penghui Sun; Wanting Wang; Xin Zeng; Bingyue Xin; Biao Zhang; Deyin Zhao; et al. (Food Bioscience, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Genome-wide association study of alkali tolerance at germination stage in wheat - Haoran Gu; Zixu Wang; Xiaotong Liu; Haotian Cao; Zixin Zhou; Meishan Zhou; Xinzhi Yang; Han Sun; Ran Qin; Chunhua Zhao; Yongzhen Wu; Fa Cui (Theoretical and Applied Genetics, 2026)

Gene editing and association analysis of circadian clock gene TaPRR59 highlights its importance in yield-related traits in wheat - Jinrong Li; Meijie Zhu; Guimei Hu; Xiaoyue Chen; Huixian Xue; Yuanxun Zhang; Yifan Wang; Ziqi Li; Dengke Xu; Mingjun Zhai; Guangsheng Zhou; Chenxiao Cui; et al. (Theoretical and Applied Genetics, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

Synergistically boosted microwave absorptive and thermal exhaustive capabilities of layered V2O5 nanofibers via Na+ intercalation - Kang Fu; Wanyi Zhou; Pinzhang Zhao; Lingling Xu; Baoxin Fan; Ran Ji; Liyan Xie; Guoxiu Tong; Tong Wu (Chemical Engineering Journal, 2026)

Deep Shale Matrix Permeability Evolution During Well Shut-In Under True Triaxial Stress - Jinzhou Zhao; Yanshan Guo; Zhihao Yu; Lan Ren; Ran Lin; Jianfa Wu; Yi Song; Cheng Shen (Rock Mechanics and Rock Engineering, 2026)

Nano-silicon mitigates sulfamethoxazole-induced stress in wheat seedlings: Integrated transcriptomic and metabolomic analysis - Qianqian Liu; Ziting Jin; Xinyu Liao; Jie Feng; Zhiheng Li; Wenlu Zhao; Yaxin Zhu; Ran Wu; Shaoting Du; Huijun Liu (Journal of Environmental Chemical Engineering, 2025)

Late Permian strike-slip tectonics in the northern North China Craton: new insights from geological and geophysical data of the Longwangmiao granitic pluton - Chao Song; Wei Lin; Wei Wei; Lingtong Meng; Yang Chu; Qinying Wu; Zhao Guo; Yin Wang; Ran An; Fei Liu; Jinhui Yang (Journal of Asian Earth Sciences, 2025)

A three-step process for purification and stability evaluation of analytical-grade phycocyanin from Spirulina - Hongxiang Zhao; Shilin Wu; Zhen Zhang; Ran Chen; Kun Li; Meicong Xiao; Yunmei Yin; Pei Wang; Rongqing Zhang (Algal Research, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

Progression of the Residual Lesion in Cavernous Sinus Extra-Axial Cavernous Hemangioma After Surgery - Ran Huo; Qifeng Yu; Hongyuan Xu; Jie Wang; Shaozhi Zhao; Jiancong Weng; Xiudan Bai; Yuming Jiao; Wenqian Zhang; Qiheng He; Zhiyou Wu; Shaowen Liu; et al. (Translational Stroke Research, 2025)

Integrated network pharmacology and cellular assay revealed an anti-type 2 diabetes effect of Astaxanthin from Haematococcus pluvialis - Ran Chen; Shilin Wu; Zhen Zhang; Kun Li; Jingyun Chen; Ning Yang; Hongxiang Zhao; Rongqing Zhang (Algal Research, 2025)

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

AdaptiveGS: an explainable genomic selection framework based on adaptive stacking ensemble machine learning - Zhen Yang; Mei Song; Xianggeng Huang; Quanrui Rao; Shanghui Zhang; Zhongzheng Zhang; Chenyang Wang; Wenjia Li; Ran Qin; Chunhua Zhao; Yongzhen Wu; Han Sun; et al. (Theoretical and Applied Genetics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Vascular-tissue-specific expression of an endo-1,4-β-xylanase enhances forage efficacy of sweet sorghum silage - Fengyong Ge; Huimin Wei; Wenzhe Zhang; Cuo Mei; Yihong Gao; Hanlei Yang; Xuekai Wang; Jingwen Cao; Zhuolin Liu; Jiayang Shi; Ran Xia; Kangxu Zhao; et al. (Molecular Plant, 2025)

Efficient inactivation of antibiotic resistant bacteria by iron-modified biochar and persulfate system: Potential for controlling antimicrobial resistance spread and mechanism insights - Ran Duan; Shuanglong Ma; Yanbing Ma; Shengjun Xu; Guangxin Li; Haichao Fu; Xujin Wu; Jinge Du; Peng Zhao (Journal of Hazardous Materials, 2025)

An ultra-sensitive, intelligent platform for food safety monitoring: Label-free detection of illegal additives using self-assembled SERS substrates and machine learning - Chunjuan Yang; Shuang Jiang; Yue Zhao; Li Zhang; Xiaoming Lyu; Shulu Zhang; Jiayue Liang; Yiyang He; Xubin Quan; Mingxu Zhang; Ran Gao; Renxing Song; et al. (Food Chemistry, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Air pollution of PM2.5-bound PAHs in urban Chongqing, China from 2015 to 2022: Concentration, source tracking and health risk - Bofei Fu; Shang Li; Shushu Lan; Xiaowei Peng; Chongjun Ran; Nanyan Li; Hong Li; Lun Xiao; Guohua Zhao; Junrui Chang; Jingxiu Han; Yunyun Wu; et al. (Urban Climate, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

Nitrogen removal and microbial metabolic analysis in an iron-carbon based constructed wetland-microbial fuel cell for mariculture wastewater treatment - Lei Wang; Tianyu Zhao; Zerui Gong; Xiaobo Ban; Zhipeng Wu; Yao Lu; Ran Jiang; Yanling Wang; Pengfei Chen; Shaobin Huang; Yongqing Zhang (Journal of Environmental Chemical Engineering, 2025)

Effect of flocculant addition and organic matter content on flocculation-electroosmotic coupled dewatering of river sludge - Qing Wei; Fuyuan Ran; Suqing Wu; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan (Journal of Environmental Chemical Engineering, 2025)

Tailoring hetero-precursor transformation for simultaneous surface-coating and subsurface-doping of Ni-rich layered oxide cathodes - Junfan Zhang; Ran Wang; Kunkun Guo; Mohan Yang; Zenan Zhao; Jing Wang; Qi Liu; Lai Chen; Ning Li; Yuefeng Su; Feng Wu; Guoqiang Tan (Chemical Engineering Journal, 2025)

Evolution of interfacial electro-chemo-mechanics in high-energy-density NCM811||Si/C-composite Lithium-ion pouch cells - He Ma; Shujun Cai; Ran Song; Kexuan Jing; Min Wu; Weizong Wang; Yurong Ren; Qian Zhao; Zhengping Ding (Chemical Engineering Journal, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

The role and function mechanism of pilV in modulating the pathogenicity of Aeromonas hydrophila - Zhengshi Zhang; Jiayan Ran; Shengfu Zhao; Hui Luo; Shuqing Zheng; Detao Li; Ziyang Li; Yongyao Yu; Hao Xu; Ronghua Wu; Hua Ye (Aquaculture, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Hesperidin alleviates endothelial cell inflammation and apoptosis of Kawasaki disease through inhibiting the TLR4/IĸBα/NF-ĸB pathway - Yuting Guan; Jinghua Ruan; Pingping Tan; Songwei Qian; Size Zhou; Ao Zhang; Yuchong Fu; Shuhui Zhao; Yuqing Ran; Xing Feng; Yijia Wang; Xinlei Wu; et al. (Chemico-Biological Interactions, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Study on the Spatial and Temporal Evolution Law of Large-Size Fracture Propagation in Deep Coalbed Based on Acoustic Emission Technology - Zhihong Zhao; Tianyu Wu; Jianchun Guo; Jiale He; Xiaoyong Wen; Yi Liu; Ran Zhang (Rock Mechanics and Rock Engineering, 2025)

Impact of flocculant compounding on dewatering of river sludge with high water content via flocculation, filter-pressing, and electro-osmotic coupled process - Fuyuan Ran; Suqing Wu; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan (Journal of Environmental Chemical Engineering, 2025)

Relative forces of anthropogenic and natural factors on the evolution of “ecological cancer”—rocky desertification under different man-land relationships - Junwei Pu; Xiaoqing Zhao; Yuju Ran; Pei Huang; Zexian Gu; Yangbin Zhang; Beihao Wu; Guoxun Qu (Environmental Monitoring and Assessment, 2025)

An active-conductive layer stacked sensor platform for real-time detection of heavy metal ions - Yuping Yang; Lijia Xu; Yongpeng Zhao; Yuchao Wang; Zhijun Wu; Zhiliang Kang; Zhiyong Zou; Hui Huang; Yong He; Fei Liu; Zuoliang Tang; Ao Feng; et al. (Chemical Engineering Journal, 2025)

Harnessing natural light: Novel nanoheterojunction photocatalyst NaGdF4:Yb,Tm@TiO2/Cu2(OH)2CO3 for actual wastewater remediation - Mengyu Di; Wenqi Liu; Dan Shan; Yue Zhao; Changyuan Zhang; Yankun Wang; Ran Yi; Yang Wu; Jing Zheng; Baiqi Wang (Journal of Environmental Management, 2024)

The restoration of karst rocky desertification has enhanced the carbon sequestration capacity of the ecosystem in southern China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Jinfeng Wang; Luhua Wu; Chaojun Li; Junhan Li; Yuanhuan Xie; Chen Ran; et al. (Global and Planetary Change, 2024)

Antimicrobial activities of natural flavonoids against foodborne pathogens and their application in food industry - Yanping Wu; Ling Jiang; Wenyi Ran; Kai Zhong; Yinglan Zhao; Hong Gao (Food Chemistry, 2024)

Biogenic silica dynamics in coastal wetland sediments: A key driver of silicon and carbon biogeochemical cycling - Xiangwei Zhao; Zhaoliang Song; Yuntao Wu; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Zimin Li; Lele Wu; Xiaomin Yang; Xiangbin Ran; Jun Sun; Yuqiu Wei; et al. (Limnology and Oceanography, 2024)
Biogenic silica (biogenic Si) is a bioactive component crucial for the biogeochemical cycling of Si in terrestrial and aquatic ecosystems. Its formation and dissolution dynamics are intricately linked to carbon (C) cycling. However, knowledge about the source, composition, and factors controlling the distribution of biogenic Si in coastal wetland sedimentary environments is still limited. To address this lack of knowledge, we introduced a suite of geometric models for biogenic Si biovolume calculation and investigated biogenic Si assemblages, along with biogenic Si and biogenic Si‐occluded C contents, in sediments from representative coastal wetlands along the west coast of Bohai Bay. Our analysis showed that sedimentary biogenic Si predominantly derived from phytoliths (78.1% ± 5.8%), diatoms (18.2% ± 4.8%), and sponge spicules (3.7% ± 2.9%). Notably, phytolith assemblages were primarily composed of forms derived from the Poaceae family. The biogenic Si‐occluded C content (0.035–1.870 g kg −1 ) within these wetland sediments was consistent across both sites, accounting for 0.97–5.71% of the total organic C pool. Structural equation modeling indicated that total organic C, pH, and amorphous aluminum oxides either directly or indirectly influenced the biogenic Si content in coastal wetlands sediments. These results demonstrate the critical role that biogenic Si plays in the Si biogeochemical cycle and provide valuable information that advances our understanding of the biogeochemical interactions between Si and C in coastal wetland ecosystems.

A framework for territorial spatial ecological restoration zoning integrating “Carbon neutrality” and “Human-geology-ecology”: Theory and application - Yuju Ran; Xiaoqing Zhao; Xianmin Ye; Xiaobao Wang; Junwei Pu; Pei Huang; Yuqin Zhou; Junyi Tao; Beihao Wu; Wenwen Dong; Guoxun Qu (Sustainable Cities and Society, 2024)

MdAP2-like, a new regulator in apple, simultaneously modulates fruit softening and size - Miaomiao Wang; Wenduo Zhan; Ming Chen; Yanfei Guo; Hao Wang; Yao Wu; Tuanhui Bai; Jian Jiao; Chunhui Song; Jiangli Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2024)

Organic matter composition and stability in estuarine wetlands depending on soil salinity - Lele Wu; Zhaoliang Song; Yuntao Wu; Shaopan Xia; Yakov Kuzyakov; Iain P. Hartley; Yunying Fang; Changxun Yu; Yidong Wang; Ji Chen; Laodong Guo; Zimin Li; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Protocatechuic acid enhanced Fe(III) activated peroxymonosulfate system for Sulfamethoxazole degradation in groundwater - Siqi Wang; Ran Wang; Qiutong Lin; Ruixin Liu; Xiaoyu Wu; Guangshan Zhang; Qi Hu; Zhao Jiang; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

EMS-induced missense mutation in TaCHLI-7D affects leaf color and yield-related traits in wheat - Zixu Wang; Huiyuan Xu; Faxiang Wang; Lingling Sun; Xiangrui Meng; Zhuochun Li; Chang Xie; Huijiao Jiang; Guangshuo Ding; Xinrong Hu; Yuhang Gao; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Efficient and low-energy degradation of chlorobenzene via catA-mediated cleavage and bedC1 docking in a novel Burkholderia stabilis TF-2 - Zhilin Xing; Fang Gou; Xiaoping Zhang; Yanhui Gao; Xihong Ke; Dongni Ran; Peng Wang; Jiangfeng Guo; Heng Wu; Chao Peng; Tiantao Zhao (Chemosphere, 2024)

Genome-wide association study and genomic selection of spike-related traits in bread wheat - Huiyuan Xu; Zixu Wang; Faxiang Wang; Xinrong Hu; Chengxue Ma; Huijiao Jiang; Chang Xie; Yuhang Gao; Guangshuo Ding; Chunhua Zhao; Ran Qin; Dezhou Cui; et al. (Theoretical and Applied Genetics, 2024)

Effects of warming on rice production and metabolism process associated with greenhouse gas emissions - Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Ke Liu; Wentao Shi; Wei Wu; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2024)

Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Chao Li; Yiyuan Ran; Pan Wu; Peng Liu; Boyi Yang; Xueyuan Gu; Ping Zhao; Shirong Liu; Lei Song; Yuhui Liu; Yizhang Liu; Zengping Ning; et al. (Journal of Hazardous Materials, 2024)

Defining the land use area threshold and optimizing its structure to improve supply-demand balance state of ecosystem services - Pei Huang; Xiaoqing Zhao; Junwei Pu; Zexian Gu; Yuju Ran; Yifei Xu; Beihao Wu; Wenwen Dong; Guoxun Qu; Bo Xiong; Longjin Zhou (Journal of Geographical Sciences, 2024)

Promoting nitrogen conversion in aerobic biotransformation of swine slurry with the co-application of manganese sulfate and biochar - Xuan Wu; Xinyu Zhao; Guorong Yi; Wanqiang Zhang; Runyu Gao; Daniel Kuok Ho Tang; Ran Xiao; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Journal of Environmental Management, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Low temperature reaction mechanism of NH3-SCR reaction on MoO modified CePO4 catalyst: Combination study on experiments and DFT calculations - Shaoxia He; Ran Zhao; Dongming Pan; Chaoyang Zhu; Wenfei Wu; Zengwu Zhao (Fuel, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

The accumulation and carbon sequestration potential of biogenic silica in coastal salt marshes: Implications for relative sea-level rise - Xiangwei Zhao; Xiaodong Zhang; Zhaoliang Song; Lukas Van Zwieten; Xiangbin Ran; Yulin Pu; Jun Sun; Qiang Li; Lele Wu; Xiaomin Yang; Yuqiu Wei; Zimin Li; et al. (CATENA, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

Na2S-modified biochar for Hg(II) removal from wastewater: A techno-economic assessment - Wenwen Zhao; Zhongsheng Zhang; Yuan Xin; Ran Xiao; Feng Gao; Haitao Wu; Wenfeng Wang; Qiang Guan; Kangle Lu (Fuel, 2024)

Effect of sesbania gum on the rheological, textural, and microstructural characteristics of CaSO4-induced soy protein isolate gels - Ran Yang; Bin Yu; Laixue Ni; Yungang Cao; Qingqing Chai; Haiteng Tao; Zheng Zhang; Guimei Liu; Yunhui Cheng; Haibo Zhao; Bo Cui; Zhengzong Wu (Food Hydrocolloids, 2024)

Characteristics of conserved microRNAome and their evolutionary adaptation to regulation of immune defense functions in the spleen of silver carp and bighead carp - Yinli Zhao; Jinxing Gu; Ran Wu; Bianzhi Liu; Pengsheng Dong; Guangqing Yu; Daoquan Zhao; Guoxi Li; Zhenjiang Yang (Fish & Shellfish Immunology, 2024)

A review of carbon nanomaterials/bacterial cellulose composites for nanomedicine applications - Yingyu Liu; Haiyan Liu; Susu Guo; Yifan Zhao; Jin Qi; Ran Zhang; Jianing Ren; Huaiyi Cheng; Mingrui Zong; Xiuping Wu; Bing Li (Carbohydrate Polymers, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Light-responsive benzobisthiazole as oxidase mimic for rapid determination of glutathione in food and vegetable - Jiao Wu; Lingbo Qu; Zhaohui Li; Linping Zhao; Yuanqiang Sun; Ran Yang (Food Chemistry, 2023)

Reply to “Comment on: Traffic-related organic and inorganic air pollution and risk of development of childhood asthma: A meta-analysis” - Yunqian Chen; Yizhuo Zhao; Zheng Ran; Chang Wang; Qiong Wu; Penghui Li; Taosheng Jin (Environmental Research, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Microplastic contamination in the dominant crabs at the intertidal zone of Chongming Island, Yangtze Estuary - Fengrun Wu; Tao Wang; Xueyan Li; Ran Zhao; Fengdong He (Science of The Total Environment, 2023)

A spectral-temporal constrained deep learning method for tree species mapping of plantation forests using time series Sentinel-2 imagery - Zehua Huang; Liheng Zhong; Feng Zhao; Jin Wu; Hao Tang; Zhengang Lv; Binyuan Xu; Longfei Zhou; Rui Sun; Ran Meng (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

The active synergetic microbiota with Aspergillus as the core dominates the metabolic network of ester synthesis in medium-high temperature Daqu - Yan Wang; Shikai Quan; Yajiao Zhao; Yu Xia; Rui Zhang; Maofang Ran; Zhengyun Wu; Wenxue Zhang (Food Microbiology, 2023)

Mapping cropland suitability in China using optimized MaxEnt model - Xiaoliang Li; Kening Wu; Shiheng Hao; Zhang Yue; Zhao Ran; Jinliang Ma (Field Crops Research, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Mapping of suitable habitats for earthworms in China - Xiaoliang Li; Kening Wu; Shiheng Hao; Long Kang; Jinliang Ma; Ran Zhao; Yue Zhang (Soil Biology and Biochemistry, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

pH-Regulated lignin as a green catalyst for Highly-Efficient CO2 cycloaddition - Yidan Ouyang; Bin Lei; Zhouqing Tan; Fen Hu; Zhao Wu; Jiaxue Wang; Yixuan Ma; Ran Zhang; Li Guo; Feifei Chen (Fuel, 2023)

Synergetic effect and mechanism of elementary sulphur, MgSO4 and KH2PO4 progressive reinforcement on pig manure composting nitrogen retention - Yang Wang; Jingwen Wang; Xuan Wu; Ran Zhao; Zengqiang Zhang; Juanjuan Zhu; Muhammad Azeem; Ran Xiao; Junting Pan; Xiu Zhang; Ronghua Li (Environmental Pollution, 2023)

Fluoride resistance capacity in mammalian cells involves global gene expression changes associate with ferroptosis - Yi Zhang; Yimin Fang; Shen Zhao; Jialong Wu; Chenkang Lu; Lai Jiang; Shujun Ran; Jia Wang; Fei Sun; Bin Liu (Chemico-Biological Interactions, 2023)

Nitrogen fertilizer alleviates rice yield loss without increasing global warming potential under elevated temperatures - Yingying Shen; Kailu Wang; Yufei Zhao; Liqing Yang; Wenzhe Liu; Tongyang Yin; Xueqin Wang; Xuan Ran; Hao Guo; Yuru Ma; Xinying Wu; Yao Chen; et al. (Field Crops Research, 2023)

Selenium/sulfur-modified montmorillonite materials mitigate mercury pollution in farmland - Shu Ran; Tianrong He; Shengpeng Li; Deliang Yin; Pan Wu; Yiyuan Xu; Jiating Zhao (Environmental Pollution, 2023)

Electroencephalogram-based objective assessment of cognitive function level associated with age-related hearing loss - Ran Zhao; Tao Yue; Zihao Xu; Yunqi Zhang; Yubo Wu; Yanru Bai; Guangjian Ni; Dong Ming (GeroScience, 2023)

QTL Detection for Internode Component Index in Wheat Using a RIL Mapping Population - Ran Qin; Tianhang Ma; Mingsu Cao; Xijian Liu; Xiaohan Zhou; Guimei Hu; Wen Zhong; Xiaohui Sun; Jingguo Xiao; Jiajin Dong; Wenchao Kong; Chunhua Zhao; et al. (Plant Molecular Biology Reporter, 2023)

C4 expansion of Central Asia in the middle Miocene linked to the strengthening Indian monsoon - Jian Wang; Xinying Zhou; Shiqi Wang; Hai Xu; Hermann Behling; Jie Ye; Yan Zheng; Junchi Liu; Yan Wu; Keliang Zhao; Ran Zhang; Xiaoqiang Li (Global and Planetary Change, 2023)

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

Elucidating the positive influence of calcined clay on the retention of carbon components during chicken manure composting - Chaonan Pan; Ran Zhao; Jin Zhou; Junqiu Wu; Liqin Wang; Yufeng Chen; Zimin Wei; Liming Jia (Process Safety and Environmental Protection, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

New insights into exogenous N-acyl-homoserine lactone manipulation in biological nitrogen removal system against ZnO nanoparticle shock - Huan Gao; Runyu Zhao; Zeyu Wu; Jinyu Ye; Lijie Duan; Ran Yu (Bioresource Technology, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

The brassinosteroid biosynthesis gene TaD11-2A controls grain size and its elite haplotype improves wheat grain yields - Huiyuan Xu; Han Sun; Jiajin Dong; Chengxue Ma; Jingxue Li; Zhuochun Li; Yihuan Wang; Junqi Ji; Xinrong Hu; Meihui Wu; Chunhua Zhao; Ran Qin; et al. (Theoretical and Applied Genetics, 2022)

Fine mapping of QFlw-5B, a major QTL for flag leaf width in common wheat (Triticum aestivum L.) - Chunhua Zhao; Xijian Liu; Hongwei Liu; Wenchao Kong; Zhuochao Zhao; Shengren Zhang; Saining Wang; Yingzi Chen; Yongzhen Wu; Han Sun; Ran Qin; Fa Cui (Theoretical and Applied Genetics, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

Numerical and Experimental Assessment of the Sandstone Fracture Mechanism by Non-uniform Bonded Particle Modeling - Kui Zhao; Wenkai Wu; Peng Zeng; Daoxue Yang; Yongguang Liu; Li Wang; Shanhu Ran (Rock Mechanics and Rock Engineering, 2021)

Temporal variation of airborne fungi in university library rooms and its relation to environmental parameters and potential confounders - Dingmeng Wu; Ying Zhang; Chenbo Zhao; Angui Li; Li’an Hou; Yu Tian; Jing Xiong; Ran Gao (Environmental Science and Pollution Research, 2021)

Marinobacter caseinilyticus sp. nov., Isolated from Saline Soil - Yanfang Nie; Xin Su; Dildar Wu; Ran Zhang; Ruijun Wang; Zhe Zhao; Maripat Xamxidin; Cong Sun; Min Wu (Current Microbiology, 2021)

Genomic sequencing and characterization of a novel group of canine bufaviruses from Henan province, China - Ran Shao; Feiyan Zheng; Siqi Cai; Jinzhao Ji; Zixin Ren; Jiawei Zhao; Liyan Wu; Jiajun Ou; Gang Lu; Shoujun Li (Archives of Virology, 2020)

Description of Erythrobacter mangrovi sp. nov., an aerobic bacterium from rhizosphere soil of mangrove plant (Kandelia candel) - Yang-Hui Ye; Nusratgul Anwar; Maripat Xamxidin; Ran Zhang; Cen Yan; Yan-Fang Nie; Zhe Zhao; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2020)

Nitratireductor mangrovi sp. nov., a Nitrate-Reducing Bacterium Isolated from Mangrove Soil - Yanghui Ye; Cen Yan; Yanfang Nie; Jianwei Zhang; Zhe Zhao; Ran Zhang; Chuan Xiao; Min Wu (Current Microbiology, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Antagonistic activity and protective effect of a Bacillus subtilis isolate against fish pathogen Edwardsiella piscicida - Xiaomeng Ren; Binbin Wu; Feng Zhao; Lingling Qi; Xianfeng Qiu; Ran Li; Sisi Yang; Fuguo Liu; Ganfeng Yi; Xuezhi Ding; Liqiu Xia; Yunjun Sun (Fisheries Science, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Analysis of status and countermeasures of cancer incidence and mortality in China - Chunchun Wu; Mengna Li; Hanbing Meng; Yukun Liu; Weihong Niu; Yao Zhou; Ran Zhao; Yumei Duan; Zhaoyang Zeng; Xiaoling Li; Guiyuan Li; Wei Xiong; et al. (Science China Life Sciences, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Indicator polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) in seafood from Xiamen (China): levels, distributions, and risk assessment - Zhuozhen Qian; Fangfang Luo; Chengye Wu; Ran Zhao; Xuan Cheng; Wenfeng Qin (Environmental Science and Pollution Research, 2017)

Cluster spacing optimization of multi-stage fracturing in horizontal shale gas wells based on stimulated reservoir volume evaluation - Ran Lin; Lan Ren; Jinzhou Zhao; Leize Wu; Yuanzhao Li (Arabian Journal of Geosciences, 2017)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)